Volatile compound composition and antioxidant activity of cooked ham slices packed in propolis-based active packaging. (June 2016) - Rizzolo, Anna; Bianchi, Giulia; Povolo, Milena; Migliori, Carmela Anna; Contarini, Giovanna; Pelizzola, Valeria; Cattaneo, Tiziana M.P.
Highlights: Paper with embedded propolis little influenced cooked ham volatiles. Lipid and non-lipid oxidation in slices in paper with on-surface propolis. Higher DPPH and reducing compounds in slices in paper with on-surface propolis. No influence on sensory properties for slices in paper with embedded propolis. Slices in paper with on-surface propolis were distinguished at triangle test. Abstract: Aiming at studying the possibility of application of propolis as food preservative, active paper sheets obtained by either surface spreading (APP) or by incorporating propolis in paper mass at 0.4% (API) were used to pack slices of cooked ham. A 4 days consumer storage simulating trial, at 4 °C, was performed and cooked ham packed with APP, API and no-propolis (control) papers was analysed for volatile composition by HS-SPME GC–MS, antioxidant properties and samples were submitted to sensory analysis (triangle test). Slices packed in API paper showed antioxidant properties similar to control slices and the gradual migration of terpenoids from packaging into ham slices did not influence the sensory properties. In contrast, in slices packed in APP paper, both DPPH radical scavenging activity and reducing compounds increased with storage, and the changes in aldehydes, ketones, carboxylic acids and alcohols amounts and composition indicated lipid and non-lipid oxidations, which impacted on the sensory characteristics of cooked ham.